PENINGKATAN KAPASITAS MASYARAKAT MELALUI PELATIHAN PUBLIC SPEAKING PADA FORUM MUDA MUDI DESA BAKULAN, CEPOGO, BOYOLALI, JAWA TENGAH - FERI SETIAWAN; FANNY HENDRO ARYO PUTRO; SRI HARTINI (KRIDA CENDEKIA, 2022)
Having the ability to communicate is the dream and dream of everyone. Communication is no longer a necessity as a social being who must interact with other people. but more than that, communication is a demand for the progress of today’s era where the world has entered the Industrial Revolution 4.0. Digital media is evidence of progress in the era of globalization. Technological advances must also be balanced with the quality of human beings in communicating. Given the importance of the ability to speak in public, then Public Speaking is the main thing and must be owned by everyone, especially for young people in a society. In socialization activities in the community, of course, requires good speaking skills. Because all jobs related to socialization require the ability to speak. For this reason, we, Boyolali University Real Work Lecturers in 2022 will hold a Public Speaking Training for Youth Organizations of Youth Organizations in Bakulan Village, Cepogo District, Boyolali Regency. With this training, it is hoped that it can help improve the quality of Public Speaking for Youth Organizations for Youth Organizations in Bakulan Village, Cepogo District, Boyolali Regency.